Pseudomonas syringae flagella displays phenotypic heterogeneity - López-Pagán, Nieves; Sánchez-Romero, María Antonia; Rufián Plaza, José Sebastián; Govantes, Fernando; Ruiz-Albert, Francisco Javier (My University, 2022)
Pseudomonas syringae is a plant-pathogenic bacteria that infects a lot of plant with economic relevance. It is ubiquitous in nature colonizing a wide range of niches including water, soil and plant phyllosphere and rhizosphere. Its life cycle is related to the water cycle and when it reaches the plant can colonize the leaf surface and entry into the apoplast by esthomes or wounds present in the leaf. For all these processes motility is considered a very important trait. On the one hand, flagellar motility has been shown to confer epiphytic advantages to P. syringae, by the other hand, in the apoplast the flagellin, a very well described pathogen-associated molecular pattern (PAMP), can be recognized by PAMPs response receptors (PRRs) triggering PAMP triggering inmunity (PTI). Using single-cell techniques such as flow cytometry and confocal microscopy we have observed that flagella is expressed heterogenously when P. syringae is growing in the apoplast and it is cross-regulated with the type III secretion system (T3SS), an essential element to suprime the PTI response. We have previously described that the T3SS expression is also heterogeneous when P. syringae is growing in the apoplast (1). Both elements are virulence genes necessary for P. syringae and their expressions generate an impact in the bacterial fitness so, as in others animals pathogen, we consider this phenotypic heterogeneity a strategy for P. syringae plant adaptation.
Keywords: Pseudomonas syringae; Pseudomonas syringae